Konsekuensi Sosial-Ekonomi Anak dari Hubungan Non-Marital dalam Tinjauan Islam - Yulianti, Yulianti (JURNAL EKONOMI DAN BISNIS (EKOBIS-DA), 2025)
The status of children born from non-marital (out-of-wedlock) relationships in Islam is a complex issue, involving tensions between classical Islamic jurisprudence (fiqh), the principles of maqāṣid al-sharī‘ah, and the demands of modern social realities. In classical fiqh, the majority of scholars maintain that a child born of zina (illicit sexual relations) may only be affiliated (nasab) with the mother, thereby excluding the child from inheritance rights, guardianship (wali) in marriage, and civil protection from the biological father. Nevertheless, Islam emphasizes that every child is born in a state of fitrah (purity) and bears no burden of the sins committed by their parents. Based on a normative-theological and ethical approach, this study finds that children born out of zina still retain fundamental rights guaranteed by the sharia, including the right to life, identity, education, and protection from discrimination. Developments in contemporary legal frameworks—including rulings by the Indonesian Constitutional Court and family law reforms in various Muslim-majority countries—reflect a shift toward a more inclusive and protective approach. Through the lens of maqāṣid al-sharī‘ah, Islamic law can be reinterpreted to uphold justice and compassion (rahmah) while preserving core sharia values. This research recommends a harmonization between classical fiqh and national legal systems to ensure comprehensive protection for out-of-wedlock children in modern Muslim societies